2020
DOI: 10.1126/sciadv.aaz6119
|View full text |Cite
|
Sign up to set email alerts
|

Label-free sensing of exosomal MCT1 and CD147 for tracking metabolic reprogramming and malignant progression in glioma

Abstract: Malignant glioma is a fatal brain tumor whose pathological progression is closely associated with glycolytic reprogramming, leading to the high expression of monocarboxylate transporter 1 (MCT1) and its ancillary protein, cluster of differentiation 147 (CD147) for enhancing lactate efflux. In particular, malignant glioma cells (GMs) release tremendous number of exosomes, nanovesicles of 30 to 200 nm in size, promoting tumor progression by the transport of pro-oncogenic molecules to neighboring cells. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 41 publications
1
76
0
Order By: Relevance
“…Glioma is a prevalent intracranial malignancy contributes to considerable cancer-related mortality 6 , 27 . Meanwhile, it is characterized by insensitive to conventional chemo-radiotherapy 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glioma is a prevalent intracranial malignancy contributes to considerable cancer-related mortality 6 , 27 . Meanwhile, it is characterized by insensitive to conventional chemo-radiotherapy 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Incidence and mortality of glioma appear to be increasing rapidly in the past few decades as a result of this highly metastatic disease [4,5]. Although the recent treatments like targeted biologic therapy and adjuvant radiotherapy have been markedly improved, overall patient survival is not satisfactory as a result of local recurrence and distant metastasis [6,7]. Thus, identification of potential pathogenic mechanisms of glioma and therapeutic approaches against glioma are significantly indispensable.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the small sample size, we found that the circulating MCT1 + CD9 + EVs in the serum reflected the tumor burden or treatment response in vivo, indicating the potential for the translation of this liquid biopsy into clinics for the management of SS. MCT1 was recently identified in exosomes derived from malignant glioma cells [ 47 ]. Thakur et al identified MCT1 mainly in the membrane of exosomes, and observed higher MCT1 expression in serum-derived exosomes from a mouse model of glioma compared to those of wild-type mice [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…MCT1 was recently identified in exosomes derived from malignant glioma cells [ 47 ]. Thakur et al identified MCT1 mainly in the membrane of exosomes, and observed higher MCT1 expression in serum-derived exosomes from a mouse model of glioma compared to those of wild-type mice [ 47 ]. These findings are consistent with our data, strongly suggesting that the detection of MCT1 on circulating serum could improve diagnosis and tumor monitoring of SS.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles (EVs) are natural nanovesicles released from most cells and biofluids; they carry various cargo including nucleic acids, proteins, and lipids [ 17 ]. EVs have attracted tremendous attention in the context of NDDS due to their ability to facilitate intracellular communication and the transportation of cargo to the target recipient cells [ 18 , 19 ]. Based on their size range and biogenesis, EVs are categorized into three major types, namely exosomes, microvesicles (MVs), and apoptotic bodies (ABs) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%